Revision of the Neotropical genus Neoscutops Malloch (Diptera: Periscelididae) - Ale-Rocha, Rosaly; Freitas, Geovânia (Zootaxa, 2011)
The Neotropical genus Neoscutops Malloch is revised and now includes 14 species. The genus is divided into two species groups: the peruvianus Group including N. annulatus sp. nov., N. barcelosiensis sp. nov., N. flavoscutellatus sp. nov., N. luteus sp. nov., N. manaos sp. nov., N. manuensis sp. nov., N. melleus sp. nov., N. nitidus sp. nov., N. peruvianus Hennig, 1969, and N. waorani sp. nov.; and the rotundipennis Group including N. cariri Amorim & Vasconcelos, 1990, N. minor sp. nov., N. ranyseae sp. nov., and N. rotundipennis Malloch, 1926. A phylogenetic analysis was performed to test the monophyly of the Neoscutops species groups proposed in this study. An identification key for the species of Neoscutops is provided.